PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN DIVISI OPERASIONAL PT. KAMIJAYA MITRA UTAMA TANGERANG - Tyas, Peni Pradityaning; Suryoko, Sri (Jurnal Ilmu Administrasi Bisnis, 2019)
Work productivity is an issue that needs serious attention from a company, because the company and employees must be take part and effort to be able to increase work productivity. PT. Kamijaya Mitra Utama is a company engaged in cleaning services. With the increasing business competition between similar companies engaged in the same field, will require companies to increase productivity. The increased of employee productivity is done by increasing motivation which can be realized by providing compensation to employees. This study aims to determine the impact of compensation and motivation on work productivity in operational division of PT. Kamijaya Mitra Utama Tangerang. The type of research used is explanatory research with the population of operational division’s employees of PT. Kamijaya Mitra Utama. The sampling technique used in this study is the saturated sample that is all 75 Operational Division employees as respondents. The technique used is quantitative analysis with the test used is the validity test, reliability test, correlation coefficient, simple and multiple regression tests, coefficient of determination, significance test (t and F test) using SPSS version 25. The results showed that there was a positive relationship between compensation and motivation on productivity, evidenced by the results of the compensation regression coefficient of 0.315 and motivation of 0.284. The compensation and motivation variables together have a positive effect on work productivity, it can be seen from the results of the F test that produces an F count (4.982)> from the F table (2.38). The researcher suggested that the reward given by PT. Kamijaya Mitra Utama needs to be improved so that employee motivation is created so that it can give a positive impact on productivity.